The Payne Index of Ministry Styles (PIMS): Ministry Styles and Psychological Type among Male Anglican Clergy in Wales - Francis, Leslie J. (Research in the social scientific study of religion, 2002)
A sample of 191 Church in Wales clergymen completed the Myers-Briggs Type Indicator alongside a new instrument intended to characterise eight preferred ministry styles based on the constructs of extraversion, introversion, sensing, intuition, thinking, feeling, judging and perceiving. The data demonstrate the usefulness of this conceptualisation of ministry styles.